Modelling and Simulation of Analogue Angular Sensors for Manufacturing Purposes - Figueiredo, Joao (2012)
This chapter develops a new mathematical model, for Pancake resolvers, which depends on a set of variables controlled by the sensor manufacturer – the winding parameters. This model allows a resolver manufacturer to manipulate in-process controllable variables in order to readjust already assembled resolvers that without any action would be scrap for the production line. The developed model follows a two-step strategy where on a first step a traditional transformer’s model computes the resolver nominal parameters and on a second step a linear model computes the corrections on the controllable variables, in order to compensate small deviations in design assumptions, caused by the variability of the manufacturing process. At the end of the chapter an experimental methodology for parameter identification and several tests for model validation are presented.